(untitled) (Bangladesh Medical Journal, 2024)
Neonatal septic arthritis (NSA) is an unusual illness, but fatal clinical condition and must be diagnosed and treated properly in order to save the neonate’s joints and life. High rate of morbidity and mortality may result from NSA if left untreated. Majority of NSA cases in developing countries present themselves late at the health care facilities, making the diagnosis difficult and sometimes overlooked by health care providers. Although septic arthritis has already been investigated but cases of NSA from developing countries are under reported. The goal of the study was to better understand the clinical and microbiological characteristics of neonates with septic arthritis as well as their prognosis of treatment. This prospective observational study was conducted in Neonatal Intensive Care Unit (NICU) of Department of Neonatology and Out Patient Department (OPD) of Orthopaedics, Banga bandhu Sheikh Mujib Medical University (BSMMU). Total 30 neonate presented with acute septic arthritis were included in this study. Data were collected by reviewing record from NICU and disease course, investigation profiles, treatment record of neonates were noted as recorded during the time of hospital stay or attending in OPD. For the assessment of prognosis clinical and radiological findings of all cases were followed-up for 12 months of age. Collected data of neonates with septic arthritis from record review were processed and analyzed by Statistical Package for the Social Sciences (SPSS) and result of analyzed, finally data were presented as in tables and graphs. This study finds that nearly two-third (63%) of the neonates were male and knee joint was most frequently involved, accounting more than two-third ( 67%) of all single joint involvements. All of the cases were anemic and had high C-reactive protein (CRP) level. Joint aspirate samples culture showed that the most prevalent (41%) organism was Klebsiella, followed by Acenotobacter and Seratia. Gram-negative bacteria predominated (91%). Most of the patient (76%) had favorable prognosis after treatment. Clinical evaluation and start of intravenous antibiotics should be given priority in suspected cases. Prompt surgical intervention and consistent follow-up in a tertiary hospital are necessary for the best results. Bangladesh Med J. 2023 Jan; 52(1): 18-23